Yoga Therapy for Improving the Quality of Life among Breast Cancer Patients: Literature Review - Rizeki Dwi Fibriansari; Laili Nur Azizah (KHD Production, 2023)
Cancer is a chronic disease that affects emotional states and changes in daily life, causing physiological and psychological problems. This condition can also affect the quality of life. This literature review aims to determine the effect of yoga therapy on improving the quality of life of breast cancer patients. The method used is by searching several published studies through databases through PubMed, Sage Journal, SpringerLink, and Science Direct. Research questions are designed using the PICO principle. Selected studies were published from 2018-2022. This yoga therapy can affect the improvement of the quality of life of breast cancer patients. Yoga can reduce depressing symptoms in patients undergoing cancer treatment and is beneficial in reducing treatment side effects, emotional improvement, and quality of life. The duration of yoga therapy, which is an average of 60 minutes, will improve the quality of life of breast cancer patients. Yoga shows significant results in improving the quality of life of breast cancer patients. Yoga can majorly affect the patient's high quality of life, namely physical function, role, emotional, cognitive, and social. Yoga interventions can relieve pain symptoms of patients undergoing cancer treatment and positively impact treatment side effects, improve emotions, and reduce the quality of life.